2007
DOI: 10.1590/s1413-86702007000300016
|View full text |Cite
|
Sign up to set email alerts
|

Vasculonecrotic reactions in leprosy

Abstract: Multibacillary, lepromatous or borderline leprosy patients may present two types of vasculonecrotic reactions: Lucio phenomenon and that associated with erythema nodosum leprosum. Despite they can be distinguished through clinical and histological characteristics; both are often used as synonyms. It is said that leprosy reaction should be properly classified for therapeutic reasons, since it is well known that in Lucio phenomenon there is not a good response to thalidomide. The authors reported two cases of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 9 publications
0
16
0
8
Order By: Relevance
“…[8] The ulcers heal with fibrotic scars. [3] Even though there have been various reports in the past of EN with necrosis occurringin untreated cases of multibacillary leprosy,[9–11] they were allassociated with fever and constitutional symptoms, which was conspicuously absent in our case.…”
Section: Discussionmentioning
confidence: 60%
“…[8] The ulcers heal with fibrotic scars. [3] Even though there have been various reports in the past of EN with necrosis occurringin untreated cases of multibacillary leprosy,[9–11] they were allassociated with fever and constitutional symptoms, which was conspicuously absent in our case.…”
Section: Discussionmentioning
confidence: 60%
“…What was odd in our patient for Lucio phenomenon was the onset of skin infarcts 4 months after starting antileprotic therapy. Lucio phenomenon is usually the presenting feature that heralds a diagnosis of leprosy [ 8 , 12 ]. Also, the presence of cutaneous infarcts in the absence of blistering or ulcerating lesions is distinctly unusual for Lucio phenomenon (Magaña et al reported a similar finding in only 3 out of 12 patients with Lucio phenomenon) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Erythema nodosum leprosum is more frequent in the first months of treatment in patients with nodules and plaques. Patients with Lucio's phenomenon do not respond well to thalidomide in contrast to erythema nodosum leprosum (45).…”
Section: New Developmentsmentioning
confidence: 95%